Vascular cognitive impairment - Bowler, John (Henry Stewart Talks, 2008)
Vascular cognitive impairment, Concepts and criteria, Epidemiology, Pathogenesis, Leukoaraiosis and infarcts, Cognitive deficit, Typical patterns and screening, Imaging, Treatment, Disease modification and symptomatic
Archived at 2021/03/30